Frontiers of cytokine engineering in CAR cell therapy for cancer - Wu, Yinghan; Li, Yan-Ruide (Frontiers in Oncology, 2026)
Chimeric antigen receptor (CAR)-engineered T (CAR-T) cell therapy has revolutionized the treatment of hematologic malignancies, yet its efficacy in solid tumors remains limited by T cell exhaustion, restricted tumor infiltration, and an immunosuppressive tumor microenvironment (TME). Recent advances in cytokine engineering have introduced innovative strategies to overcome these barriers by modulating CAR cell survival, persistence, and cytotoxic function. This review provides a comprehensive analysis of emerging cytokine-augmented CAR platforms, highlighting mechanistic innovations such as IL-2 superkines that enhance selective CAR-T expansion, IL-15–armed CAR constructs that sustain in vivo persistence, and IL-12 and IL-18 co-expression systems that remodel the TME and recruit endogenous immune effectors. The roles of IL-7, IL-10, and IL-21 in preserving memory phenotypes, mitigating exhaustion, and improving metabolic fitness are also discussed in depth. Furthermore, the review explores synthetic and inducible cytokine circuits that enable spatial and temporal control of cytokine release, improving therapeutic precision and reducing systemic toxicity. Collectively, these innovations represent a paradigm shift toward next-generation, cytokine-engineered CAR therapies with enhanced efficacy, safety, and durability against both hematologic and solid tumors.